Seed dispersal networks in tropical forest fragments: Area effects, remnant species, and interaction diversity - Emer, Carine [UNESP]; Jordano, Pedro; Pizo, Marco A. [UNESP]; Ribeiro, Milton C. [UNESP]; da Silva, Fernanda R.; Galetti, Mauro [UNESP] (Wiley, 2020)
Seed dispersal interactions involve key ecological processes in tropical forests that help to maintain ecosystem functioning. Yet this functionality may be threatened by increasing habitat loss, defaunation, and fragmentation. However, generalist species, and their interactions, can benefit from the habitat change caused by human disturbance while more specialized interactions mostly disappear. Therefore, changes in the structure of the local, within fragment, networks can be expected. Here we investigated how the structure of seed dispersal networks changes along a gradient of increasing habitat fragmentation. We analyzed 16 bird seed dispersal assemblages from forest fragments of a biodiversity-rich ecosystem. We found significant species–, interaction–, and network–area relationships, yet the later was determined by the number of species remaining in each community. The number of frugivorous bird and plant species, their interactions, and the number of links per species decreases as area is lost in the fragmented landscape. In contrast, network nestedness has a negative relationship with fragment area, suggesting an increasing generalization of the network structure in the gradient of fragmentation. Network specialization was not significantly affected by area, indicating that some network properties may be invariant to disturbance. Still, the local extinction of partner species, paralleled by a loss of interactions and specialist–specialist bird–plant seed dispersal associations, suggests the functional homogenization of the system as area is lost. Our study provides empirical evidence for network–area relationships driven by the presence/absence of remnant species and the interactions they perform. Abstract in Spanish is available with online material.
Keywords: Atlantic Forest; defaunation; forest fragmentation; Frugivory; human disturbance; network-area relationship; species interactions